Development of A Sustainable Consumption Model of Corn Plant Through A Circular Economic Approach (Case study of the processing program of corn stalks into alternative fuel to replace coal for CSR SIG Tuban Factory) - Luksono Luksono; Susanto Susanto (Return : Study of Management, Economic and Bussines, 2024)
In Tuban, farmers have great potential to manage corn cob waste into alternative fuels, but there is still a lack of experience and awareness of waste management. This research aims to develop an educational model that can increase the utilization of waste. The method used is Design-Based Research (DBR) with a qualitative approach, including problem identification, needs analysis, model development, and model testing through workshops. The survey results show that most farmers have not managed corn cob waste properly. The workshop succeeded in increasing farmers' knowledge about waste management and producing alternative fuel products. The educational model developed is effective in increasing farmers' awareness and skills in waste management. In conclusion, this sustainable consumption education model is effective in increasing the use of corn cob waste as an alternative fuel. For long-term success, it is necessary to pay attention to the aspects of technology, flexibility of participation, and freedom of expression in the Generation Z farming community.